2010
DOI: 10.1111/j.1460-9592.2009.03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐elective intraosseous infusion after failed intravenous access in pediatric anesthesia1

Abstract: IO access represents a quick and reliable alternative for pediatric patients with prolonged difficult or failed IV access after inhalational induction of anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 21 publications
0
15
0
3
Order By: Relevance
“…Studies have demonstrated that IO use can decrease the time needed to obtain vascular access in pediatric patients in cardiac arrest [6,8] and that the success of vascular access in this patient population is higher for IO access (83%) than for saphenous venous cutdown (81%), subclavian central line (77%), and percutaneous peripheral (17%) [9]. Although typically used in the emergency and critical care settings, IO access can also be used in the perioperative setting [10]. Historically, IO use was recommended only in children younger than 6 years; however, its use in infants, pediatric, and adult patients has been supported by recent literature, as well as guidelines for cardiopulmonary resuscitation and trauma [11][12][13].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have demonstrated that IO use can decrease the time needed to obtain vascular access in pediatric patients in cardiac arrest [6,8] and that the success of vascular access in this patient population is higher for IO access (83%) than for saphenous venous cutdown (81%), subclavian central line (77%), and percutaneous peripheral (17%) [9]. Although typically used in the emergency and critical care settings, IO access can also be used in the perioperative setting [10]. Historically, IO use was recommended only in children younger than 6 years; however, its use in infants, pediatric, and adult patients has been supported by recent literature, as well as guidelines for cardiopulmonary resuscitation and trauma [11][12][13].…”
Section: Discussionmentioning
confidence: 98%
“…Intraosseous access can be considered clinically appropriate on the basis of a shortterm need for patients • with chronic disease who have been admitted to the hospital for treatment of a medical event, for example, the deteriorating patient with chronic obstructive pulmonary disease; • with limited vascular access due to aggressive treatment modalities, for example, fistulas, grafts, shunts, mastectomies, or multiple central catheter placements; • for whom Rapid Response Teams are called to prevent an emergent situation and in whom obtaining peripheral or central IV access is difficult; • who experience an unexpected medical event that causes their peripheral or central IV device to become nonfunctional, for example, infiltration or occlusion, and difficult to reestablish; • who have limited peripheral access due to morbid obesity; • who suffer from intractable pain; • who are in the early stages of sepsis; • who are receiving palliative or hospice care; • who are undergoing anesthesia and experience prolonged, difficult, or failed IV access. 26,27 …”
Section: Clinical Situations In Which Io Access May Be Consideredmentioning
confidence: 98%
“…Therefore, there are more and more case reports and recommendations for its use not only in the prehospital emergency situation but also for perioperative pediatric anesthesia care [14,22,29,31,32,34,[39][40][41][42][43][44][45][46]. As a consequence of these reports and in order to provide a structured approach, the German Scientific Working Group for Pediatric Anesthesia published working guidelines in 2011 for the use of intraosseous infusion in the pediatric perioperative setting [37].…”
Section: Intraosseous Infusion In Pediatric Anesthesiamentioning
confidence: 99%